DAMPAK LEVERAGE TERHADAP PENGARUH CORPORATE GOVERNANCE DAN SOCIAL RESPONSIBILITY PADA NILAI PERUSAHAAN - Safitri, Ruticha; Asyik, Nur Fadjrih (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to examine the influence of good corporate governance (GCG) and corporate social responsibility (CSR) to the firm value and company characteristic as the moderating variable. The population is all companies which are listed in Indonesia Stock Exchange (IDX). The samples are all food and beverages which are listed in Indonesia Stock Exchange during 2011-2015 periods. The total research samples are 12 food and beverages companies which have been selected by using purposive sampling. The analysis method has been done by using multiple linear analysis technique. The good corporate governance is measured by using managerial ownership, corporate social responsibility by using CSR index, firm value by using price book value (PBV) and company characteristic is measured by using leverage with debt equity ratio (DER). The result of the research shows that good corporate governance does not have any influence to the firm value and Corporate social responsibility does not have any influence to the firm value. The leverage has significant negative impact to the influence of corporate governance (GCG) to the firm value and The leverage does not have any impact to the influence of corporate social responsibility (CSR) to the firm value.Keywords: good corporate governance, corporate social responsibility, leverage, firm value.